Performance Comparison of Transmission Control Protocol and User Datagram Protocol over Wireless Networks - Mohammed Hasan, Ali; Mohamad Fadli, Zolkipli; Aws Naser, Jaber (2015)

(untitled)
Network access over WiFi primarily depends on the access point that provides a mesh network and allows a peer-to-peer connectivity mode. This study measures the performance of Transmission Control Protocol (TCP) and User Datagram Protocol (UDP) over WiFi. Various network-related issues such as packet loss, error control, and reliability are measured. From the NS2 results, UDP provides better results for real-time data in WiFi networks than TCP. Loss of packets or data occurs when UDP is used. However, the throughput of UDP is higher than that of TCP because during a handover, the TCP window size is reset, thus decreasing the throughput. Further, the handover latencies for TCP are higher than those for UDP.